Lupe Anguiano: She Empowers the Poor - Carol Clark:::::: (Today's Parish)
When you meet Lupe Anguiano, the vigor of her step, the direct look in her eyes, the determination in her voice, tell you she is a woman of power and purpose. As the daughter of migrant workers from Mexico, she has learned not only to empathize with the poor, but to respect them.